2014
DOI: 10.1109/tfuzz.2014.2298053
|View full text |Cite
|
Sign up to set email alerts
|

Fault Tolerant Controller Design for T–S Fuzzy Systems With Time-Varying Delay and Actuator Faults: A K-Step Fault-Estimation Approach

Abstract: This paper is concerned with the problem of robust fault estimation and fault-tolerant control for a class of Takagi-Sugeno (T-S) fuzzy systems with time-varying state delay and actuator faults. Based on the (k − 1)th fault estimation information, a novel k-step fault-estimation observer is proposed to construct the kth fault error dynamics. The obtained fault estimates via k-step fault-estimation can practically better depict the size and shape of the faults. Then, based on the information of online k-step fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(129 citation statements)
references
References 49 publications
0
129
0
Order By: Relevance
“…It can be concluded that the obtained results in this paper are less conservative than those of [4,7], [34][35][36]. Moreover, if we assume timevarying delay .t/ satisfies (2), the delay-dependent fault estimation conditions proposed in [21][22][23][24][25], [27] fail to give a feasible solution. However, by using LMI toolbox in matlab, a feasible solution of Theorem 3.1 can be obtained for .t/ D 1 C 0:1si nt.…”
Section: Numerical Examplementioning
confidence: 76%
See 2 more Smart Citations
“…It can be concluded that the obtained results in this paper are less conservative than those of [4,7], [34][35][36]. Moreover, if we assume timevarying delay .t/ satisfies (2), the delay-dependent fault estimation conditions proposed in [21][22][23][24][25], [27] fail to give a feasible solution. However, by using LMI toolbox in matlab, a feasible solution of Theorem 3.1 can be obtained for .t/ D 1 C 0:1si nt.…”
Section: Numerical Examplementioning
confidence: 76%
“…If there is no state delay, then (3) reduces to the existing one in [30]. Moreover, the lower bound of delay is not restricted to 0 as [23], which is even more applicable to networked control systems and other practical systems.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this subsection, an MS-FE approach is developed according to the aforementioned work by Huang and Yang 25 and Zhang et al 26 With such fault estimation method, the estimation result can approximate the true value more precisely while the rapidity is guaranteed. The whole estimate scheme is shown in Figure 2.…”
Section: Multiple-step Actuator Fault Estimation Approachmentioning
confidence: 99%
“…The type-II T-S fuzzy sets can provide additional redundancy in modeling progress, which enhances the capability of the system to handle parameter uncertainties. An MS-FE algorithm is proposed in light of the works by Huang and Yang 25 and Zhang et al 26 Several conditions of fault value in Liu et al 27 such as f ðtÞ 2 L 2 ½0; 1Þ is not necessary, instead the assumption _ f ðtÞ 2 L 2 ð0; 1Þ is considered in this algorithm. And the estimation result from each step is used for the next estimation part, and such kind of "iteration" is helpful to enhance the estimation accuracy and ensure the speed.…”
Section: Introductionmentioning
confidence: 99%